Gorlin-Goltz syndrome: Happenstance finding- A case report - Khooshbu Gayen; Sagar L Pabale; Paras Angrish; Supreet Shailesh Shirolkar; Subir Sarkar (Wolters Kluwer Medknow Publications, 2021)
Gorlin-Goltz syndrome (GGS), due to its sparse occurrence in various populations along with the variety of associated signs and symptoms, very often becomes a missed diagnosis. The most commonly associated triad with GGS is that of multiple odontogenic keratocysts in the jaws, skeletal abnormalities, and multiple basal cell nevus carcinomas. In many cases, each of these conditions is treated separately and the recognition of underlying syndrome is rare or happenstance. The case reported here is rare of its kind as it has been diagnosed in the first decade of life, thus avoiding the possibility of morbidity in later life in the form of neoplasia and hostile basal cell carcinomas. As per our knowledge, no case had yet been reported at this early age and it emphasizes the importance of pedodontist in early recognition of the syndrome.